Proceso de recolección y comercialización de hongos comestibles silvestres en el Valle de Toluca, México - Mariaca Méndez, Ramón; Silva Pérez, Luz del Carmen; Castaños Montes, Carlos Alberto (CIENCIA ergo-sum; Vol. 8 Núm. 1 (2001): CIENCIA ergo-sum (marzo-junio 2001), 2015)
In Mexico, human consumption of edible fungi has occurred since the time of the Pre Columbian cultures. Historians of the sixteenth century and beyond have described the use of fungi as well as the manner in which they were classified. Presently, in the rural areas of Mexico, more than two hundred edible varieties are registered as being harvested, with different ethnic groups having a vast knowledge about them. The present study took place in the Valley of Toluca, with the intention of understanding the phenomena of harvesting fungi, as well as the process of their commercialization. The study took place from 1994 to 1996, taking into account four trips accompanying harvesters in the Valley as well as in mountains bordering the valley, and in three markets. Of the thirty four taxa encountered, all had been reported previously an indication of their persistence.